Perception of sport science undergraduates on the jigsaw learning method / Hoe Wee Eng and Fong Cheng Wei - Eng, Hoe Wee; Wei, Fong Cheng (Universiti Teknologi MARA, 2021)
Recognising the potential of Jigsaw Learning Method (JLM) and limited research around its uses in higher education, this case study sought to explore the perceptions of sport science students' on learning using the JLM. A total of 36 undergraduate students enrolling in the Sport and Exercise Psychology Course participated in this study. They were divided into groups and participated in JLM using a 2-hour lecture on 'addictive and unhealthy behaviours' with JLM materials uploaded into the Google Classroom. At the end of the JLM session, a reflective essay was carried out to find out students' learning experience. The analysis of the perceptions of the students on JLM revealed two main themes which were 'learning experience of JLM' and 'perceptions of their own and others' abilities'. JLM is perceived as an effective learning strategy but students were concerned on the issue of deliverable content and accuracy of the team members' responses. In this study, with its limitation, JLM proved that classroom learning could be educational and enriching.